Micafungin vs. Posaconazole Prophylaxis in Patients with Acute Leukemia or Myelodysplastic Syndrome: A Randomized, Open-label Study. (4th October 2017) - Epstein, David J; Seo, Susan; Huang, Yao-Ting; Park, Jae; Kimek, Virginia; Tallman, Martin S; Frattini, Mark G; Papanicolaou, Genovefa
Abstract: Background: Antifungal prophylaxis is routinely administered to patients with acute leukemia (AL) or myelodysplastic syndrome (MDS) with neutropenia from intensive chemotherapy (ICT). Posaconazole is effective prophylaxis, but is often not feasible. Micafungin, an appealing alternative, has never been prospectively compared with posaconazole in this setting. Methods: Patients with AL or MDS undergoing ICT were randomized (1:1) to receive open-label micafungin 100 mg intravenously daily or posaconazole suspension 400 mg orally twice daily until neutrophil recovery or maximum of 28 days. The primary endpoint was prophylaxis failure (premature prophylaxis discontinuation due to antifungal therapy, intolerance, adverse event, or death). Time to failure was calculated by Kaplan-Meier analysis. The log-rank test was used for comparison between the arms. Results: From March 2011 to May 2016, 113 patients who received at least 2 doses of prophylaxis were analyzed (58 patients randomized to micafungin and 55 patients to posaconazole). Prophylaxis failure occurred in 34.5% and 52.7% of patients on micafungin and posaconazole, respectively (P = 0.0118). The median number of days on prophylaxis was 16 [interquartile range (IQR) 12–20] for micafungin and 13 [IQR 6–16] for posaconazole (P = 0.01). Antifungal therapy accounted for 95% of failures for micafungin and 41.4% for posaconazole; with 44.8% of posaconazole failures attributed to intolerance or possible poor absorption. Empiric therapy of fever and neutropenia accounted for the majority of antifungal therapy. Probable and definite breakthrough fungal infections were rare and similar in both arms. Conclusion: Our data support micafungin as an alternative agent for antifungal prophylaxis during neutropenia in patients with AL and MDS. Disclosures: Y. T. Huang, Merck & Co.: Grant Investigator, Research grant; M. G. Frattini, Astellas: Scientific Advisor, Advisor honorarium; Merck: Scientific Advisor, Advisor honorarium; G. Papanicolaou, Astellas Pharma: Consultant and Grant Investigator, Consulting fee, Research grant and Research support; Merck &Co: DSC member and Investigator, Consulting fee, Research grant and Research support